Meneropong Upaya Qur’anisasi Masyarakat Kampung di Ujung Timur Pulau Jawa (Studi Living Qur’an) - Lestari, Puput (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This article is an observation that the author made while in Banyuwangi. Banyuwangi, which historically was a city that used to be predominantly Hindu, has now turned into a predominantly Muslim and religious city. This study focuses on observing the habit of reading the Koran in the community of one of the villages in Banyuwangi. Some observations were made in the month of Ramadan, and some were carried out outside the month of Ramadan. Then in collecting data, the author conducted interviews with one of the local Koran teachers and some of the observations made by the authors when participating in some of these activities. From the results of research and observations made by the author, it turns out that there is an interesting side that displays the piety of the villagers. Among them, the application of the practice of the values of the Koran through the reading of the Koran in various forms and is considered the heart of worship. The various forms of reading the Koran start from reading the Koran in the month of Ramadan combined with local cultural traditions, and several sima'an Koran assemblies that were established collectively that have a unique and distinctive feel.